2019
DOI: 10.1136/rmdopen-2017-000585
|View full text |Cite
|
Sign up to set email alerts
|

Predicting adherence to therapy in rheumatoid arthritis, psoriatic arthritis or ankylosing spondylitis: a large cross-sectional study

Abstract: ObjectiveThis analysis explored the association of treatment adherence with beliefs about medication, patient demographic and disease characteristics and medication types in rheumatoid arthritis (RA), psoriatic arthritis (PsA) or ankylosing spondylitis (AS) to develop adherence prediction models.MethodsThe population was a subset from ALIGN, a multicountry, cross-sectional, self-administered survey study in adult patients (n=7328) with six immune-mediated inflammatory diseases who were routinely receiving syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 41 publications
(29 reference statements)
5
59
2
3
Order By: Relevance
“…We found that anti-TNF adherence did not differ between patients with different types of CIR; this finding contrasted with the findings of Smolen et al, who demonstrated identical anti-TNF adherence in patients with RA and PsA, but worse adherence in patients with AS. 1 In our study, adherence was not impacted by the disease duration or to the number of sessions attended by the patient. However, adherence was better in older subjects than in younger subjects, consistent with Smolen et al In addition, that study showed that anti-TNF adherence was improved among patients that believed the treatment would be effective, compared to those that worried about the inherent risks of treatment, based on the Beliefs about Medicine Questionnaire.…”
Section: Discussionsupporting
confidence: 40%
See 4 more Smart Citations
“…We found that anti-TNF adherence did not differ between patients with different types of CIR; this finding contrasted with the findings of Smolen et al, who demonstrated identical anti-TNF adherence in patients with RA and PsA, but worse adherence in patients with AS. 1 In our study, adherence was not impacted by the disease duration or to the number of sessions attended by the patient. However, adherence was better in older subjects than in younger subjects, consistent with Smolen et al In addition, that study showed that anti-TNF adherence was improved among patients that believed the treatment would be effective, compared to those that worried about the inherent risks of treatment, based on the Beliefs about Medicine Questionnaire.…”
Section: Discussionsupporting
confidence: 40%
“…This finding was consistent with the good adherence level reported by Smolen et al (70.6-74.1%), in a study of 3390 patients (RA: n=1943; AS: n=812, PsA: n=635), based on the Morisky MMAS-4© questionnaire. 1 However, Smolen et al did not report whether those patients benefitted from TPE. We found that anti-TNF adherence did not differ between patients with different types of CIR; this finding contrasted with the findings of Smolen et al, who demonstrated identical anti-TNF adherence in patients with RA and PsA, but worse adherence in patients with AS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations